2001
DOI: 10.1046/j.1365-2389.2001.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Humus composition of soils under forest, coffee and arable cultivation in hilly areas of south Sumatra, Indonesia

Abstract: Summary To understand the effect of land use changes on the composition of humus in tropical soils, samples from land under primary forest, secondary forest, coffee plantation, and arable crops were investigated at three sites in south Sumatra, Indonesia. Total carbon and total nitrogen contents were 1.7 to 4.3 times and 1.1 to 2.8 times greater in the topsoil under primary forest than under the other types of land use. Following change from primary forest to other uses, the proportion of humic acids in the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 27 publications
6
24
1
2
Order By: Relevance
“…In our study, the HA/FA ratio varied from 0.32 to 3.90 and from 0.28 to 10.29 for grasslands and arable lands, respectively, indicating differences in the intensity of OC humification processes and mobility of C in the soils (Figure a,b). Our results correspond to studies Watanabe, Rumbanraja, Tsutsuki, and Kimura (), You et al. (), Shen et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the HA/FA ratio varied from 0.32 to 3.90 and from 0.28 to 10.29 for grasslands and arable lands, respectively, indicating differences in the intensity of OC humification processes and mobility of C in the soils (Figure a,b). Our results correspond to studies Watanabe, Rumbanraja, Tsutsuki, and Kimura (), You et al. (), Shen et al.…”
Section: Discussionsupporting
confidence: 93%
“…The higher proportion of HA/FA for grassland soils indicated higher humification rates. Additionally, HI values >1 (for most of the soils) indicated that the HA fraction persisted longer in the soil (Moraes et al., ; Watanabe et al., ). A low DT can be related to a strong interaction between the SOM and the soil mineral phase, resulting in high SOM stability in the more recalcitrant humin fractions (Guimaraes et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In PI, the soil showed a wider C/N ratio, followed by SW and finally the annual cropping. These results are in agreement with the available literature, in which the replacement of the native vegetation by annual croppings leads to this difference (Watanabe et al 2001;Leite et al 2003b). Also, utilization of N fertilization has contributed to this fact, since the N loss by leaching in clay soils is less; therefore, N remains in the system and leads to a closer C/N ratio.…”
Section: Total C and Nsupporting
confidence: 92%
“…The soil N TN contents were reduced, similar to C TOC , after the slash and burn of the savannah. Almost all studies carried out in savannahs have proven this result (Watanabe et al 2001;Freixo et al 2002;Leite et al 2003bLeite et al , 2003cWendling et al 2005).…”
Section: Total C and Nmentioning
confidence: 76%
“…24 O cultivo de cafeeiro em área originalmente sob floresta primária, recém-desmatada, acarretou uma diminuição dos teores de C-AH e aumento de C-AF na superfície, enquanto que, em subsuperfície, houve diminuição de ambas as frações. 25 Na sub-bacia do Rio das Mortes, há uma expressiva escassez de dados a respeito da influência dos diferentes manejos das culturas implantadas sobre as propriedades da matéria orgânica do solo. Assim, este trabalho teve como objetivo avaliar a qualidade química da matéria orgânica do solo mais expressivo geograficamente dessa sub-bacia, cultivado com cafeeiro, sob manejos convencional e orgâ-nico, por meio de indicadores com níveis variáveis de sensibilidade às operações de preparo e cultivo do solo, que exercem forte influência sobre a dinâmica da matéria orgânica e de seus compartimentos (C orgânico total, C da fração leve e C nas frações ácidos húmico e fúlvico), tendo como referência solo sob mata nativa.…”
Section: Introductionunclassified